Incidence of value motivational strategies on high school students’ cognitive and metacognitive strategies - Suárez Riveiro, José Manuel; Fernández Suárez, Ana Patricia; Rubio Sánchez, Verónica; Zamora Menéndez, Ángela (Revista Complutense de Educación, 2015)
The main purpose of this study was to propose a model of how self-regulation motivational strategies related to the value component affect the use of cognitive and metacognitive learning strategies. The sample was made up 1103 Spanish-speaking secondary students. It was assumed that the effect of motivational strategies on cognitive strategies can be mediated by metacognitive strategies. Results showed, on the one hand, significant effects from some motivational strategies, but not from all of them, towards self-regulation and towards cognitive strategies. On the other hand, results show the significant effects of learning metacognitive strategies on all of cognitive strategies. It may be concluded that it is convenience for students not to adopt not only cognitive and metacognitive strategies but also other strategies, some of the self-motivation strategies, which will allow them to manage their own motivation and thus improve their learning.